2006
DOI: 10.1007/bf02859278
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial burden in thalassemia

Abstract: There is tremendous psychosocial disease burden perceived by the affected adolescents and hence it is imperative to ameliorate it by promoting a clear understanding of the disease and initiating intervention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 7 publications
3
36
2
3
Order By: Relevance
“…Promotion of social knowledge, regular clinical checkups and modern treatment strategies could help to increase the hopes and life expectancy of thalassemic patients. 32 Our study was limited by the lack of a control group, and therefore we were unable to compare the QoL scores of thalassemic patients with similar scores in a normal population. In addition, because this was a patient population in a single referral institution, the results may not be representative of patients in…”
Section: Discussionmentioning
confidence: 98%
“…Promotion of social knowledge, regular clinical checkups and modern treatment strategies could help to increase the hopes and life expectancy of thalassemic patients. 32 Our study was limited by the lack of a control group, and therefore we were unable to compare the QoL scores of thalassemic patients with similar scores in a normal population. In addition, because this was a patient population in a single referral institution, the results may not be representative of patients in…”
Section: Discussionmentioning
confidence: 98%
“…Also, they suffer from decreased self-esteem, feelings of difference from others, poor self-image, need to be dependent, and anxiety problems (7). In the study by Messina et al (8), severe psychological problems in young adults with thalassemia major were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Thalassemia is the most common hematological disease that has no definitive cure (1). According to available statistics, each year approximately 60,000 children are born with thalassemia worldwide (2).…”
Section: Introductionmentioning
confidence: 99%
“…The work of Verschueren et al showed that a significant relationship exists between social acceptance and positive self-concept (10). Similarly, Khurana et al (2006) showed that 68% of children with thalassemia status didn't feel good about their skeletal status and were not satisfied with their mental picture, which also led to low selfconcept. Almost all of them referred to their physical appearance as a major cause of their frustration (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation